Gender Differences in Plagiarism Attitudes among Indonesian University Students in Perth Australia - Lilis Ummi Fa'iezah (JOURNAL OF EDUCATION, 2009)
One of the major problems faced by a university nowadays is plagiarism. The problem of plagiarism is found not only in Indonesian universities but also in overseas universities. Lecturers in overseas universities often find papers containing copy and paste sentences. This study aims to investigate plagiarism attitudes among Indonesian university students in Perth, Western Australia. Further, this study also intends to investigate differences in plagiarism attitudes between male and female Indonesian students. The results of this research may help Indonesian students to realize and understand that plagiarism relates to the academic dishonesty. Moreover, students must understand that achieving good grades is important but presenting the original masterpieces from the good sources of their own knowledge is more important.